Exploitation vs. exploration—computational temporal and semantic analysis explains semantic verbal fluency impairment in Alzheimer's disease. (August 2019) - Tröger, Johannes; Linz, Nicklas; König, Alexandra; Robert, Philippe; Alexandersson, Jan; Peter, Jessica; Kray, Jutta
Abstract: Impaired Semantic Verbal Fluency (SVF) in dementia due to Alzheimer's Disease (AD) and its precursor Mild Cognitive Impairment (MCI) is well known. Yet, it remains open whether this impairment mirrors the breakdown of semantic memory retrieval processes or executive control processes. Therefore, qualitative analysis of the SVF has been proposed but is limited in terms of methodology and feasibility in clinical practice. Consequently, research draws no conclusive picture which of these afore-mentioned processes drives the SVF impairment in AD and MCI. This study uses a qualitative computational approach—combining temporal and semantic information—to investigate exploitation and exploration patterns as indicators for semantic memory retrieval and executive control processes. Audio SVF recordings of 20 controls (C, 66–81 years), 55 MCI (57–94 years) and 20 AD subjects (66–82 years) were assessed while groups were matched according to age and education. All groups produced, on average, the same amount of semantically related items in rapid succession within word clusters. Conversely, towards AD, there was a clear decline in semantic as well as temporal exploration patterns between clusters. Results strongly point towards preserved exploitation—semantic memory retrieval processes—and hampered exploration—executive control processes—in AD and potentially in MCI. Highlights: AD patients show no impairment in semantic memory exploitation patterns in the SVF. AD and MCI patients show impairments in exploration of semantic memory in the SVF. AD patients show impairment in executive control but preserved semantic memory. Novel temporal and semantic computational information are fused to analyze the SVF.